Dynamics of corticospinal changes during and after high‐intensity quadriceps exercise. Issue 8 (25th June 2014) - Gruet, Mathieu; Temesi, John; Rupp, Thomas; Levy, Patrick; Verges, Samuel; Millet, Guillaume Y.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Progressive development of the supraspinal component of central fatigue and increases in corticospinal excitability and inhibition have been demonstrated during fatiguing contractions of the elbow flexors. However, the kinetics of mechanical and EMG responses induced by transcranial magnetic stimulation during and after single‐joint fatiguing knee‐extensor exercise remains unknown. What is the main finding and its importance? Our results show that single‐joint knee‐extensor isometric exercise induces late supraspinal fatigue with increased intracortical inhibition, both of which recover quickly after task failure, and unchanged corticospinal excitability. This indicates that fatigue‐induced corticospinal changes are muscle and/or limb specific and reinforces the need to measure corticospinal changes within seconds after task failure to avoid their underestimation. This study tested the hypothesis that during fatiguing quadriceps exercise, supraspinal fatigue develops late, is associated with both increased corticospinal excitability and inhibition and recovers quickly. Eight subjects performed 20 s contractions [15 s at 50% maximal voluntary contraction (MVC) followed by 5 s MVC] separated by a 10 s rest period until task failure. Transcranial magnetic stimulation (TMS) and electrical femoral nerve stimulation (PNS) were delivered ∼2 s apart during 50% MVC, during MVC and after MVC in relaxed muscle. Voluntary activation was assessed by TMS (VATMS) immediately before and after exercise and then three times over a 6 min recovery period. During exercise, MVC and twitch force evoked by PNS in relaxed muscle decreased progressively to 48 ± 8 and 36 ± 16% of control values, respectively (both P < 0.01). Significant changes in voluntary activation assessed by PNS and twitch evoked by TMS during MVC were observed during the last quarter of exercise only (from 96.4 ± 1.7 to 86 ± 13%, P = 0.03 and from 0.76 ± 0.8 to 4.9 ± 4.7% MVC, P = 0.02, from baseline to task failure, respectively). The TMS‐induced silent period increased linearly during both MVC (by ∼79 ms) and 50% MVC (by ∼63 ms; both P < 0.01). Motor‐evoked potential amplitude did not change during the protocol at any force levels. Both silent period and VATMS recovered within 2 min postexercise, whereas MVC and twitch force evoked by PNS in relaxed muscle recovered to only 84 ± 9 and 73 ± 17% of control values 6 min after exercise, respectively. In conclusion, high‐intensity single‐joint quadriceps exercise induces supraspinal fatigue near task failure, with increased intracortical inhibition and, in contrast to previous upper‐limb results, unchanged corticospinal excitability. These changes recover rapidly after task failure, emphasizing the need to measure corticospinal adaptations immediately at task failure to avoid underestimation of exercise‐induced corticospinal changes.